2022
DOI: 10.1002/adma.202110604
|View full text |Cite
|
Sign up to set email alerts
|

Synergic Reaction Kinetics over Adjacent Ruthenium Sites for Superb Hydrogen Generation in Alkaline Media

Abstract: Ruthenium (Ru)‐based electrocatalysts as platinum (Pt) alternatives in catalyzing hydrogen evolution reaction (HER) are promising. However, achieving efficient reaction processes on Ru catalysts is still a challenge, especially in alkaline media. Here, the well‐dispersed Ru nanoparticles with adjacent Ru single atoms on carbon substrate (Ru1,n‐NC) is demonstrated to be a superb electrocatalyst for alkaline HER. The obtained Ru1,n‐NC exhibits ultralow overpotential (14.8 mV) and high turnover frequency (1.25 H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(89 citation statements)
references
References 45 publications
(73 reference statements)
1
82
0
Order By: Relevance
“…Zhang et al synthesized an electrocatalyst containing both Ru single atoms and nanoparticles anchored on defective carbon via a Ru–alginate metal-organic supramolecules conversion method . Song et al synthesized well-dispersed Ru nanoparticles with adjacent Ru single atoms on a carbon substrate (Ru 1, n -NC) through the pyrolysis of Ru-anchoring polypyrrole at high temperature . The atomic dispersed Ru in the substrate can significantly reduce the adsorption capacity of active hydrogen, , while Ru nanoparticles can reduce the dissociation energy of water.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al synthesized an electrocatalyst containing both Ru single atoms and nanoparticles anchored on defective carbon via a Ru–alginate metal-organic supramolecules conversion method . Song et al synthesized well-dispersed Ru nanoparticles with adjacent Ru single atoms on a carbon substrate (Ru 1, n -NC) through the pyrolysis of Ru-anchoring polypyrrole at high temperature . The atomic dispersed Ru in the substrate can significantly reduce the adsorption capacity of active hydrogen, , while Ru nanoparticles can reduce the dissociation energy of water.…”
Section: Introductionmentioning
confidence: 99%
“…CC BY 4.0. Panels (c–e) are adapted with permission from (c) ref and (d, e) ref . Copyright 2021 and 2022, respectively, Wiley-VCH.…”
Section: Catalysis By Nano-single-atom-site Catalystsmentioning
confidence: 94%
“…Song et al reported an NSASC with Ru NPs and Ru single atoms on a carbon substrate (Ru 1,n -NC) that exhibited excellent activity in alkaline HER. 113 The electron interaction between Ru NPs and Ru 1 sites endowed Ru-NSASCs with stronger H 2 O dissociation ability and weaker OH adsorption energy than Ru 1 sites and Ru NPs, which was beneficial to the desorption of OH to release active sites. The energy barriers of water activation were 0.05 and 0.30 eV on the Ru 1 site and Ru NPs in Ru-NSASCs, respectively, which are much lower than those on single Ru 1 sites and Ru NPs (0.40 and 0.95 eV, respectively) (Figure 11d,e).…”
Section: Catalysis By Nano-single-atom-site Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher initial potential for CO oxidation represented a weaker hydroxide adsorption on Ru@M-OH and thus implied an enhanced water activation capability for improved HER in alkaline media. 30 In addition, the electrochemical surface area was evaluated by double-layercapacitance (DLC) measurement. Figures 3d and S6 illustrate the enlarged area obtained on Ru@M-OH, suggesting that more active sites were activated and generated by the OH −modified Ru intercalation approach.…”
mentioning
confidence: 99%